2017
DOI: 10.1002/jbm4.10025
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin Antibody Treatment Stimulates Bone Formation to Normalize Bone Mass in Male Down Syndrome Mice

Abstract: Down syndrome (DS), characterized by trisomy of human chromosome 21, is associated with a variety of endocrine disorders as well as profound skeletal abnormalities. The low bone mass phenotype in DS is defined by low bone turnover due to decreased osteoclast and osteoblast activity, decreasing the utility of antiresorptive agents in people with DS. Sclerostin antibody (SclAb) is a therapeutic candidate currently being evaluated as a bone anabolic agent. Scl, the product of the sclerostin gene (SOST), inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…To test if acute depletion of SOST changed hematopoiesis, we performed studies in which SOST was depleted using sclerostinspecific antibodies (Scl-Ab), administered subcutaneously in 8-week-old mice in multiple doses for 6 weeks ( Figure 1A). Scl-Ab treatment resulted in increased trabecular volume BV/TV and midshaft cortical thickness, similar to that observed in the Sost -/mice ( Figure 1B, 1C and 1D) (41,42). However, the BM total cellularity was unchanged (data not shown).…”
Section: Sclerostin-depleting Antibody Treatment Changes Hematopoietisupporting
confidence: 82%
“…To test if acute depletion of SOST changed hematopoiesis, we performed studies in which SOST was depleted using sclerostinspecific antibodies (Scl-Ab), administered subcutaneously in 8-week-old mice in multiple doses for 6 weeks ( Figure 1A). Scl-Ab treatment resulted in increased trabecular volume BV/TV and midshaft cortical thickness, similar to that observed in the Sost -/mice ( Figure 1B, 1C and 1D) (41,42). However, the BM total cellularity was unchanged (data not shown).…”
Section: Sclerostin-depleting Antibody Treatment Changes Hematopoietisupporting
confidence: 82%
“…To test if acute depletion of SOST changed hematopoiesis, we performed studies in which SOST was depleted using sclerostin-specific antibodies (Scl-Ab), administered subcutaneously in 8-week-old mice in multiple doses for 6 weeks (Figure 1A). Scl-Ab treatment resulted in increased trabecular volume/total volume (BV/TV) and midshaft cortical thickness, similar to that observed in the Sost −/− mice (Figure 1B-D) [34,39]. However, the BM total cellularity was unchanged (data not shown).…”
Section: Sclerostin-depleting Antibody Treatment Changes Hematopoietic Differentiationsupporting
confidence: 75%
“…Previous studies have shown that sclerostin antibodies can be used to treat osteoporosis and skeletal abnormalities, increasing bone formation, bone mass and bone strength . Additionally, sclerostin antibodies have been reported to promote fracture callus formation and increase the stability of internal fixation .…”
Section: Discussionmentioning
confidence: 99%